2016
DOI: 10.1177/1534735416681641
|View full text |Cite
|
Sign up to set email alerts
|

Safety of Combined Treatment With Monoclonal Antibodies and Viscum album L Preparations

Abstract: Combination strategies involving chemotherapy and monoclonal antibodies (mAb) are commonly used in attempts to produce better clinical outcomes. This practice has led to new and ongoing toxicities that may lead to reductions in dose or noncompliance, limiting the effectiveness of treatment. Viscum album L (VA) preparations are widely used in Europe as additive therapy and have been associated with reduced chemotherapy-related adverse reactions and increased health-related quality of life. Concomitant VA therap… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
23
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 45 publications
8
23
0
4
Order By: Relevance
“…Thus, the immunomodulatory nature of VA raises the question of whether there are immunologic interactions between VA and inhibitors of the PD-1/PDL-1 or CTLA-4 pathways that might lead to increased toxicity for cancer patients. On the other hand recent results of our group revealed that the adverse event rate of targeted therapy was significantly reduced in cancer patients when VA was concomitantly applied [30]. This is in line with the observation that VA is applied in integrative oncology concepts concomitantly to adjuvant antineoplastic treatment to improve tolerability of chemotherapy-induced toxicity [24,39,40].…”
Section: Introductionsupporting
confidence: 74%
See 1 more Smart Citation
“…Thus, the immunomodulatory nature of VA raises the question of whether there are immunologic interactions between VA and inhibitors of the PD-1/PDL-1 or CTLA-4 pathways that might lead to increased toxicity for cancer patients. On the other hand recent results of our group revealed that the adverse event rate of targeted therapy was significantly reduced in cancer patients when VA was concomitantly applied [30]. This is in line with the observation that VA is applied in integrative oncology concepts concomitantly to adjuvant antineoplastic treatment to improve tolerability of chemotherapy-induced toxicity [24,39,40].…”
Section: Introductionsupporting
confidence: 74%
“…With regards to adverse effects the safety profile of VA has indicated that subcutaneous (s.c.) and intravenous (i.v.) applications of VA in cancer were safe with no serious AEs [30][31][32][33]. A meta-analysis of clinical studies that applied VA Iscador preparations concluded that it might have beneficial effects in psychosomatic self-regulation in addition to short-term quality of life-improving effects in cancer patients [34].…”
Section: Introductionmentioning
confidence: 99%
“…Die Ergebnisse einiger weniger hierzu bisher durchgeführter Untersuchungen weisen darauf hin, dass Mistelextrakte kein oder nur ein geringes Risiko für klinische Interaktionen aufweisen. Es handelt sich dabei vorwiegend um präklinische Studien [40][41][42][43][44][45][46]. Eine erste Phase-I-Studie zeigte für ein Mistelpräparat am Patienten, dass die Pharmakokinetik des Zytostatikums Gemcitabin bei paralleler Anwendung von hohen Dosierungen bis zu 250 mg Mistelextrakt nicht beeinflusst wurde [47].…”
Section: Interaktionenunclassified
“…Außerdem bestärkt diese Untersuchung, dass man eine Misteltherapie sehr gut auch parallel zur Chemotherapie einsetzen kann. Dies konnten bereits andere Studien zeigen, nämlich dass keine Wechselwirkungen zwischen einer Misteltherapie und einer schulmedizinischen Therapie über bestimmte Leberenzyme der Cytochrom-P450-Gruppe zu erwarten sind [7,8] und dass eine Misteltherapie während einer Checkpointinhibitorund Antikörpertherapie eingesetzt werden kann [9,10].…”
Section: Gfbkkommentarunclassified